Wpływ mediów na kształtowanie postaw politycznych młodzieży (wyniki badań) - Lebiotkowski, Andrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The shaping of social and political attitudes is one of the key tasks to be fulfilled by the media. Such attitudes influence our behavior, emotional reactions and the perception of our surrounding reality. The survey was inspired by the question of whether the media influence the political attitudes of the youth and, if so, to what extent? The survey was designed to cover high school students in the final year. The survey did not concern a specialized high school with 25 students in the final year. It was conducted in October 2008. The method applied to the Opalenica High School students’ study involved surveying by means of a questionnaire with a set of replies provided. The respondents proved to have a knowledge of political issues. The question arises, where does this knowledge come from? One can venture to answer that, whether directly or indirectly, this knowledge is mainly derived from the media.